Cloud Workload Analysis with SWAT - Breternitz, Mauricio; Lowery, Keith; Charnoff, Anton; Kaminski, Patryk; Piga, Leonardo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2012: Anais do XXIV International Symposium on Computer Architecture and High Performance Computing, 2012)
This note describes the Synthetic Workload Application Toolkit (SWAT) and presents the results from a set of experiments on some key cloud workloads. SWAT is a software platform that automates the creation, deployment, provisioning, execution, and (most importantly) data gathering of synthetic compute workloads on clusters of arbitrary size. SWAT collects and aggregates data from application execution logs, operating system call interfaces, and micro architecture-specific program counters. The data collected by SWAT are used to characterize the effects of network traffic, file I/O, and computation on program performance. The output is analyzed to provide insight into the design and deployment of cloud workloads and systems. Each workload is characterized according to its scalability with the number of server nodes and Hadoop server jobs, sensitivity to network characteristics (bandwidth, latency, statistics on packet size), and computation vs. I/O intensity as these values adjusted via workload-specific parameters. (In the future, we will use SWAT's benchmark synthesizer capability.) We also characterize micro-architectural characteristics that give insight on the micro architecture of processors better suited for this class of workloads. We contrast our results with prior work on Cloud Suite [5], validating some conclusions and providing further insight into others. This illustrates SWAT's data collection capabilities and usefulness to obtain insight on cloud applications and systems.